Adverse Fetomaternal Outcomes in Pregnant Females with Hepatitis C Virus Infection (Journal of Fatima Jinnah Medical University, 2018)
Background: Hepatitis C is caused by the hepatitis C virus ( HCV ) which affects the liver primarily and is infective too. Globally , HCV is a major health problem in developed and developing countries and is a major source of patients’ misery, causing an enormous burden on health care system. Hepatitis Ciscaused a RNA virus of family Flaviviridae, and genus Flavivirus, is a single stranded, enveloped and spherical virus. Objective: To determine the adverse fetomaternal outcomes in pregnant females with Hepatitis C virus. Material & Methods: This descriptive case series was done on 125 pregnant women with hepatitis C. Hepatitis C was confirmed with ELISA method. Fetomaternal outcomes were assessed after delivery. Results: The mean age of patients was 30.15±5.07 years. The mean gestational age was 35.02±1.70 weeks. PROM was observed in 14 (11%) patients, preterm delivery was occurred in 21 (17%) cases while low birth weight was observed in 21 (16.8%) respondents. The mean Apgar score of respondents was 5.62±1.053. There were 32 (25.6%) females who had normal vaginal delivery whereas 93 (74.4%) females had cesarean section. Conclusion: It was concluded through results of this study that Hepatitis C had impact on maternal outcome and had risk of developing obstetrical complications like preterm labour, PROM, and on fetal outcome like low birth weight and low APGAR scores. Hepatitis C was found to be more in patients having previous surgeries so it is recommended that patients having Hepatitis C infection should be delivered in tertiary care hospital with good nursery facilities. Sterilization techniques should be improved to decrease the burden of Hepatitis C disease in pregnant patients.
Keywords: Hepatitis C and Pregnancy, Fetomaternal outcome H, Low Birth Weight, Poor Apgar